Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Kemampuan Penalaran Matematis Siswa Kelas VII SMP PAB 13 Stabat : The Influence of the Contextual Teaching and Learning (CTL) Model on the Mathematical Reasoning Abilities of Grade VII Students at SMP PAB 13 Stabat - Mardiana, Mardiana; Mardiati, Mardiati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aimed to determine whether there is an influence of the Contextual Teaching and Learning (CTL) model on the mathematical reasoning abilities of grade VII students at SMP PAB Stabat. This research was conducted at SMP PAB Stabat during the odd semester, with the population consisting of all grade VII students. The method used in this study was a quasi-experiment with a pretest-posttest control group design. The sampling technique used was simple random sampling, from which two classes were selected as the sample: class VII-2 as the experimental group and class VII-3 as the control group. The prerequisite tests included the Lilliefors test for data normality and the Fisher's test for data homogeneity. Data analysis was conducted using a t-test. Based on the prerequisite tests and subsequent analysis, it was found that there is an influence of the CTL learning model on the mathematical reasoning abilities of grade VII students at SMP PAB Stabat.